2015
DOI: 10.1039/c4gc01398k
|View full text |Cite
|
Sign up to set email alerts
|

Dioxomolybdenum(vi) complex immobilized on ascorbic acid coated TiO2 nanoparticles catalyzed heterogeneous oxidation of olefins and sulfides

Abstract: TiO2/AA/MoO2 nanocomplex demonstrated desired activity and selectivity in the epoxidation of olefins and oxidation of sulfides to sulfoxides using H2O2 as an environmentally benign oxidant in ethanol as a green solvent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 68 publications
0
15
0
1
Order By: Relevance
“…[15][16][17] Therefore, a large number of methods, procedures and oxidizing agents have been proposed for this type of transformation. [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] Despite the fact that amines such as aniline, pyridine and … are not an appropriate catalyst for the oxidation reactions, they can effectively modify the catalytic activity of the molybdates and molybdenum oxides due to the electronic interactions between these amines and the active sites in the hybrid structures. However, majority of these traditional protocols rely on the use of hazardous terminal oxidants with low content of effective oxygen, and high cost which can generate hazardous by-products.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[15][16][17] Therefore, a large number of methods, procedures and oxidizing agents have been proposed for this type of transformation. [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] Despite the fact that amines such as aniline, pyridine and … are not an appropriate catalyst for the oxidation reactions, they can effectively modify the catalytic activity of the molybdates and molybdenum oxides due to the electronic interactions between these amines and the active sites in the hybrid structures. However, majority of these traditional protocols rely on the use of hazardous terminal oxidants with low content of effective oxygen, and high cost which can generate hazardous by-products.…”
Section: Introductionmentioning
confidence: 99%
“…This feature has stimulated the development of useful procedures for H 2 O 2 oxidation with various types of catalytic systems. [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] Despite the fact that amines such as aniline, pyridine and … are not an appropriate catalyst for the oxidation reactions, they can effectively modify the catalytic activity of the molybdates and molybdenum oxides due to the electronic interactions between these amines and the active sites in the hybrid structures. [12,14,[46][47][48][49] In recent years, owing to the redox properties of ceria, various types of ceria-based catalysts including cerium (IV) triflate, [50] ammonium cerium (IV) nitrate, [51] immobilized cerium alkyl phosphonate [52] and heterobimetallic cerium (IV) oxo clusters [53] are also widely used in selective oxidation of sulfides.…”
Section: Introductionmentioning
confidence: 99%
“…The observed peaks at 1755 and 1673 cm -1 could be correlated to the C=O and C=C stretching modes [23]. In addition, peak at 1320 cm -1 describes the (O-H) enediol in free acid that in the spectrum of SiO 2 -CA-AA is missing, due to the O C3 and O C2 atoms coordinated to CA and possibly SiO 2 NPs [24]. In the case of SiO 2 -CA-AA presence of the peak at 1733 cm -1 shows that carbonyl groups of CA and AA fixed on the surface of SiO 2 .…”
Section: Ft-ir Spectroscopymentioning
confidence: 99%
“…[84] Ther esults for 1%Au@SiO 2 and benchmark SiO 2 are listed in Table 3. [86] Theoxidation of alcohols is afrequently used reaction to test the potential of new heterogeneous catalysts.I ts importance resulted in many reports covering basically all areas of solid materials such as polyoxometalates, [87] metal oxides, [88] clays [89] and deposited transition metals [90] as catalysts.P erovskites are porous mineral structures with ageneral formula ABO 3 ,Aand Bbeing, respectively asmall high-charged and alarge low-charged cation. In terms of the preparation method it was found that the procedure which provides the smallest particles (sol-immobilization) gave the best results.I ng eneral, smaller rings are more reactive towards oxidation, hence higher temperatures were used for the larger ones.T his effect is caused by the degree of reorganization required to form ap lanar allyl radical and is independent of the catalyst system.…”
Section: Angewandte Chemiementioning
confidence: 99%